Thioxopyrimidine in Heterocyclic Synthesis III: Synthesis and Properties of Some Novel Heterocyclic Chalcone Derivatives Containing a Thieno[2,3-d]pyrimidine-Based Chromophore - Yuh Wen Ho; Wei Hua Yao (Journal of Chemistry)
Cyclization of 4-methyl-2-phenyl-6-thioxo-1,6-dihydropyrimidine-5-carbonitrile 1 with chloroacetone in DMF in the presence of excess potassium carbonate anhydrous gave the 1-(5-amino-4-methyl-2-phenylthieno[2,3-d]pyrimidin-6-yl)ethanone 3, which can react with 2,5-dimethoxytetrahydrofuran in glacial acetic acid producing the 1-[4-methyl-2-phenyl-5-(1H-pyrrol-1-yl)thieno[2,3-d]pyrimidin-6-yl]ethanone 4. On the other hand, a series of novel 3-aryl-1-[4-methyl-2-phenyl-5-(1H-pyrrol-1-yl)-thieno[2,3-d]pyrimidin-6-yl]prop-2-en-1-one chalcone dyes 6a—n were obtained by the condensation reaction of 1-[4-methyl-2-phenyl-5(1H-pyrrol-1-yl)thieno[2,3-d]-pyrimidin-6-yl]ethanone 4 with appropriate aldehydes. The structures of chalcone dyes were characterized by IR, 1H NMR, mass, elemental analysis, and UV-Vis spectroscopy. The dyes were applied to polyester fibers for creating hues ranging from greenish-yellow to orange; their spectral characteristics, substituent effect in DMF solution, fastness properties, and colorimetric assessment are also discussed.